Clays and Clay Minerals, Vol. 56, No. 4, 461–469, 2008. - Castaldi, Paola; Silvetti, Margherita; Santona, Laura; Enzo, Stefano; Melis, Pietro (The Clay Minerals Society, 2008)
The present work shows the results of X-ray diffraction (XRD), Fourier transform infrared (FTIR), and thermal analysis of untreated (RMnt) and acid-treated red mud (RMa), a bauxite ore-processing waste, exchanged with Pb2+, Cd2+, and Zn2+ cations. These studies were performed in order to investigate the changes in the sorbent structure caused by the exchange with metals of different ionic radii. The XRD pattern of RMnt, analyzed according to the Rietveld method, showed a mixture of eight different phases. However, just three phases made up 78 wt.% of the RMnt: cancrinite (33 wt.%), hematite (29 wt.%), and sodalite (16 wt.%). X-ray diffraction patterns of RMnt exchanged with Pb2+ and Cd2+ cations revealed two additional phases, namely hydrocerussite [Pb3(CO3)2(OH)2 (10 wt.%)] and octavite [CdCO3 (8 wt.%)]. These two phases probably originated from the carbonate precipitation processes which were due to the decarbonation of cancrinite. Hydrocerussite and octavite were not found in the case of acid-treated red mud samples. In the FTIR spectra, the introduction of cations caused a distinct shift to higher wavenumbers in the peak at ~1100 cm-1, which is attributed to the asymmetric stretch of Si-O-Al. This effect may be associated with the Pb2+, Cd2+, and Zn2+ adsorbed by the red muds which caused a deformation of the initial structure. Thermal analysis data of the red mud samples were obtained by thermogravimetric/differential thermogravimetric analysis, and these methods were employed to evaluate the desorption behavior of water and to clarify the thermal stability of the chemical phases of the different red mud samples. The loss of metal-bound water in the red mud samples was found to depend on the size of non-framework cations and water loss consistently followed the order: Zn2+>Cd2+>Pb2+.
Xrd, Ftir, And Thermal Analysis Of Bauxite Ore-processing Waste (red Mud) Exchanged With Heavy Metals.
Clays and Clay Minerals, Vol. 56, No. 4, 461–469, 2008. Xrd, Ftir, And Thermal Analysis Of Bauxite Ore-processing Waste (red Mud) Exchanged With Heavy Metals. Paola Castaldi; Margherita Silvetti; Laura Santona; Stefano Enzo; Pietro Melis. DOI: 10.1346/CCMN.2008.0560407. Copyright © 2008, The Clay Minerals Society.
Keywords: Periodicals; Geology; Cancrinite; Cations of Pb2+, Cd2+, and Zn2+; Hydrocerussite; Octavite; Red muds; Sodalite